Does the development of fintech promote debt risk? Evidence from East Java province - Wardhana, Angga Restu; Indriyani, Diyan (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Developments of financial technology have an impact on economic growth and people’s income. The rapid development of fintech has the impact of increasing financial inclusion or debt risk. This study aims to determine the impact of fintech on consumption behaviour and debt risks in East Java. The research data is from January 2019 - December 2020 with fintech variables, online loans, consumption levels, and debt risk. The research methods used are SVAR and OLS to provide an explanation of the impact of fintech on consumption behaviour and debt risk. The results of the research, fintech in the short-run restriction does not directly affect consumption levels, but in the long-run restriction, it directly affects consumption. Fintech will affect consumption through online lending. On the other hand, fintech has a significant effect on loan risk. The policy mix between related institutions can increase the positive role of fintech and mitigate loan risk.